Weber and Coyote: Polytheism as a Practical Attitude. - Larvor, Brendan (Sophia, 2020)
Hyde claims that the trickster spirit is necessary for the renewal of culture, and that he lives only in the 'complex terrain of polytheism'. Fortunately for those of us in monotheistic cultures, Weber gives reasons for thinking that polytheism is making a return, albeit in a new, disenchanted form. The plan of this paper is to elaborate some basic notions from Weber (rationalisation, disenchantment, bureaucracy), to explore Hyde's thesis in more detail and then to take up the question of the plurality of spirits both around and within us and whether the trickster is one of them. Weber has three roles in this argument. First, he theorises rationalisation, disenchantment and bureaucracy; second, he offers an argument that in a certain sense polytheism is returning (if it ever went away); and third, he presents a way to translate the mytho-poetic register in which Hyde works into terms acceptable to social science of a more materialist bent. The claim of the paper is that polytheism as a practical attitude means recognising that there are diverse and contradictory ethical orders built into the world around us and active with our psyches. Weber explains why this is especially difficult for us (because our lives are so thoroughly rationalised), and Hyde offers us the hope that we may be tricky enough to cope.